2019
DOI: 10.1039/c9ra06426e
|View full text |Cite
|
Sign up to set email alerts
|

Light-controlled two-dimensional TiO2 plate micromotors

Abstract: In this work, UV light-controlled two-dimensional (2D) TiO 2 plate micromotors are demonstrated for the first time. The 2D TiO 2 micromotors are produced by the well-known anodic oxidation method in combination with a cracking and separation process. When the motor is placed in H 2 O 2 aqueous solution under UV irradiation, oxygen bubbles are generated in the holes of the TiO 2 membrane. The 2D micromotor thus moves upon O 2 bubbles under its own weight. In contrast to bubble-propelled micromotors, which requi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 48 publications
0
14
0
Order By: Relevance
“…Successive bubble ejection from one opening of the tubular TiO 2 micromotors result in sequential recoil forces leading to propulsion (Figure 2A). Similarly, lightdriven TiO 2 nanotube arrays and TiO 2 plates have also been reported [20,21]. However, Chen and colleagues were the first to show phototaxis of isotropic micromotors based on asymmetric light irradiation (Figure 2B) [8].…”
Section: Single-component Titania Mnmsmentioning
confidence: 83%
“…Successive bubble ejection from one opening of the tubular TiO 2 micromotors result in sequential recoil forces leading to propulsion (Figure 2A). Similarly, lightdriven TiO 2 nanotube arrays and TiO 2 plates have also been reported [20,21]. However, Chen and colleagues were the first to show phototaxis of isotropic micromotors based on asymmetric light irradiation (Figure 2B) [8].…”
Section: Single-component Titania Mnmsmentioning
confidence: 83%
“…The surfactant could reduce the surface tension of the micromotor, leading to a higher particle speed. 36,37 However, use of more than 7 wt % retarded the displacement of JWSP@TMPN@JGO x presumably because of the changes in the viscosity of the solution. 38 Such motion trajectories and speeds of JWSP@TMPN@ JGO x were evaluated quantitatively with and without visible light irradiation (Figure 11).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The displacement of JWSP@TMPN@JGO x increased as the surfactant concentration increased from 0 to 7 wt %. The surfactant could reduce the surface tension of the micromotor, leading to a higher particle speed. , However, use of more than 7 wt % retarded the displacement of JWSP@TMPN@JGO x presumably because of the changes in the viscosity of the solution …”
Section: Results and Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that TiO 2 -based nanotube bundles stand as a versatile, smart, and biocompatible platform for tissue engineering, drug delivery, and biosensing. [20] Although there are a few works on microrobots based on TiO 2 nanotube bundles, [27,28] these require UV photoactivation, a high concentration of H 2 O 2 (10% wt. ), and/or surfactants.…”
Section: Introductionmentioning
confidence: 99%